Persepsi Orang Tua Terhadap Peran Guru Agama Dalam Membentuk Akhlak Anak Di Lingkungan Perumahan - Arie Nurdiansyah; Yesi Widiya Sari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study is to determine how parents perceive the role of religion teachers in shaping the morals of children in the Warnasari Cilegon Housing neighborhood. Children in this neighborhood lack an understanding of morals at home and outside the home due to a lack of parental times and knowledge about religion. This qualitative study uses primary data sources, such as parents and religious teachers, and secondary data sources, such as religious and community leaders in Warnasari Housing Cilegon. Data will be collected through unstructured interviews, participant observation, and documentation. The data will be analyzed using data reduction, data presentation, and conclusion drawing. The results of this study show that religious teachers act as mentors, role models, educators, and advisors for children in the Warnasari Cilegon Housing community. Parents perceive religious teachers positively because they influence children's behavior and discipline in worship. Thus, religious teachers play a role in shaping children's morals in the Warnasari Cilegon Housing environment, and parents have positive perceptions of religious teachers.